Apology Strategy in English By Native Speaker - Mezia Kemala Sari (Lingua Cultura, 2016)
This research discussed apology strategies in English by native speaker. This descriptive study was presented within the framework of Pragmatics based on the forms of strategies due to the coding manual as found in CCSARP (Cross-Cultural Speech Acts Realization Project).The goals of this study were to describe the apology strategies in English by native speaker and identify the influencing factors of it. Data were collected through the use of the questionnaire in the form of Discourse Completion Test, which was distributed to 30 native speakers. Data were classified based on the degree of familiarity and the social distance between speaker and hearer and then the data of native will be separated and classified by the type of strategies in coding manual. The results of this study are the pattern of apology strategies of native speaker brief with the pattern that potentially occurs IFID plus Offer of repair plus Taking on responsibility. While Alerters, Explanation and Downgrading appear with less number of percentage. Then, the factors that influence the apology utterance by native speakers are the social situation, the degree of familiarity and degree of the offence which more complicated the mistake tend to produce the most complex utterances by the speaker.